Gambaran motivasi dan status psikososial pada mahasiswa yang melakukan dan tidak melakukan perawatan ortodontik di Fakultas Kedokteran Universitas Udayana - Komang Ayu Sri Widyasanthi; Louise Cinthia Hutomo; Adijanti Marheni (Bali Dental Journal, 2018)
Background: Appealing facial appearance holds an important role in increasing self confidence and social perception. Problems on facial appearance can be caused by dento-facial conditions and can be restored by undergoing orthodontic treatment. Aim: The aim of this study is to find out motivation and psychosocial status on college student underwent and do not underwent orthodontic treatment in Medical Faculty of Udayana University. Methods: Cross sectional designed were used as design of this study with total 165 respondents (female = 122, male = 43), age ranged from 18-23 years old. Data were collected using PIDAQ questionnaire. Results: Result from questionnaire will categorize respondents based on status and history of orthodontic treatment, motivation, and psychosocial status. Treatment status is divided into those who underwent treatment (n=81) and those who did not undergo treatment (n=84), motivation is divided into having motivation (n=114) and do not have motivation to undergo orthodontic treatment (n=50). Strongest motive that was had by those who still undergoing treatment and those who has finisihed treatment was dental condition (n= 24; n=25). On the other hand, strongest motive that was had by those who do not undergo treatment was facial appearance/aesthetic (n=18). IOTN score was used on someone to asses the need of dental treatment. Mild IOTN score were the majority on those underwent treatment (n=65) and those who did not undergo treatment also had mild IOTN score as the majority (n=74). Psychosocial status is categorized into good (n=102), moderate (n=55), dan low (n=8). In groups whose underwent treatment, only two respondents had low psyschosocial status and six respondents had low psychosocial status within those did not undergo treatment group. Conclusion: Based on the result of the study, it can be concluded that the strongest motivation to conduct orthodontic treatment is that the willing to improve facial appearance and dental condution. Highest psychosocial status is had by those who do not undergo orthodontic treatment.